2015
DOI: 10.1517/14728222.2016.1113260
|View full text |Cite
|
Sign up to set email alerts
|

The urokinase-type plasminogen activator (uPA) system as a biomarker and therapeutic target in human malignancies

Abstract: Because of promising results obtained from previous preclinical studies, several clinical trials aimed at inhibiting the expression or function of uPA/uPAR have been completed or are ongoing. In these trials, favorable outcomes in reducing metastatic spread and extending the lifespan of cancer patients have been reported, and no severe adverse events were observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
109
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 161 publications
4
109
0
Order By: Relevance
“…Cancer is the result of a series of genetic or epigenetic regulations, and environmental risk factors may contribute to the development and progression of tumors [21, 43]. Thus, in-depth understanding of the mechanisms underlying carcinogenesis is needed to characterize genetic alterations linked to OSCC development [44].…”
Section: Discussionmentioning
confidence: 99%
“…Cancer is the result of a series of genetic or epigenetic regulations, and environmental risk factors may contribute to the development and progression of tumors [21, 43]. Thus, in-depth understanding of the mechanisms underlying carcinogenesis is needed to characterize genetic alterations linked to OSCC development [44].…”
Section: Discussionmentioning
confidence: 99%
“…During the progress of a metastasis, it is critical that cancers cells secrete the proteases for digesting ECM and allow themselves to migrate to other tissues or organs . Previous studies have revealed that two MMPs (MMP‐2 and MMP‐9) are highly expressed in various types of malignant tumors .…”
Section: Discussionmentioning
confidence: 99%
“…The proteolytic events of the metastasis process involve various proteases, such as serine proteinase, plasminogen activator, cathepsin and matrix metalloproteinases (MMPs) (Cheng et al, 2016;Su et al, 2016;Yeh et al, 2016;Su et al, 2017). MMPs are a family of zinc-dependent endopeptidases that are collectively capable of degrading most components of the basement membrane and ECM, and increased expressions of these enzymes are detected in almost all human cancers and have been associated with the aggressiveness of various neoplasms (Cox et al, 2001;Shuman Moss et al, 2012).…”
Section: Introductionmentioning
confidence: 99%